HUBUNGAN USIA DAN PARITAS TERHADAP KECEMASAN PADA IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN DI PUSKESMAS PAYUNG SEKAKI PEKANBARU TAHUN 2025 - Gestya Indah Gamela; Cecen Suci Hakameri; Rika Andriyani; Juli Selvi Yanti; Sherly Vermita Warlenda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Anxiety among third-trimester pregnant women approaching childbirth is a psychological problem that can negatively affect both maternal and fetal health. Various factors such as age, education, parity, income, husband’s support, knowledge, and support from health workers are suspected to influence anxiety levels. This study aimed to identify the factors affecting anxiety among third-trimester pregnant women in facing childbirth at Payung Sekaki Public Health Center, Pekanbaru, in 2025. This study employed a descriptive analytic design with a cross-sectional approach. The study sample consisted of third-trimester pregnant women who attended antenatal care at Payung Sekaki Public Health Center, Pekanbaru. Data were collected using a structured questionnaire and analyzed using the Chi-Square test. The results showed that there were significant relationships between husband’s support (p = 0.003), level of education (p = 0.015), age (p = 0.004), parity (p = 0.030), family income (p = 0.020), maternal knowledge (p = 0.024), and support from health workers (p = 0.038) with anxiety levels among third-trimester pregnant women. The factors influencing anxiety among third-trimester pregnant women approaching childbirth include husband’s support, education, age, parity, income, knowledge, and support from health workers. It is expected that health workers can enhance education and counseling for pregnant women and involve family members, especially husbands, in efforts to reduce anxiety before childbirth.Keywords: Anxiety, Pregnant Women, Third Trimester, Childbirth, Influencing Factors